(untitled) (Altre Modernità, 2018)
The growth of global migration flows does not only reshape territories towards superdiversity and transnationalism (Crul et al 2012) ; it also influences peopleʼs everyday life in an educational way (Tramma 2015). The merging of different cultural systems, together with the multiplication of opportunities for women and the increasing insecurity of the life course, challenges the traditional dichotomies – native/foreigner, man/woman, adulthood/youth – and requires from everyone the capability of building a self-made biography (Beck 1998) in a system of multiple belongings. The biographies of young women with a migrant background seem to be an important object of attention: these stories are an example of the intersectionality of gender-based, generational and intercultural dynamics. Furthermore, these youngsters are involved in a permanent renegotiation of meanings and in the daily crossing of real and symbolic borders: they grew up juggling different cultural expectation and racialized gender norms (Pyke, Johson 2003). The domain of educational sciences is challenged by this population: because the girls need to develop some specific skills – of syntheses, creativity and negotiation – in order to actively participate within their social context; and because institutions providing formal education, such as schools and social care services, need to re-discuss their traditional models and praxis, in order to recognise and promote the value of these mixed biographies.